Find the next number in the following sequence.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Employing Fubini Theorem, the nth term is defined by the following: k = 1 ∑ n 2 k ( k + 1 ) = k = 1 ∑ n j = 1 ∑ k j = j = 1 ∑ n k = j ∑ n j = j = 1 ∑ n j ( n + 1 − j ) = k = 1 ∑ n k ( n + 1 − k ) = k = 1 ∑ n k ( ( n + 2 ) − ( k + 1 ) )
k = 1 ∑ n 2 k ( k + 1 ) = ( n + 1 ) k = 1 ∑ n k − 2 k = 1 ∑ n 2 k ( k + 1 ) = ( n + 2 ) 2 n ( n + 1 ) − 2 k = 1 ∑ n 2 k ( k + 1 ) = 2 n ( n + 1 ) ( n + 2 ) − 2 k = 1 ∑ n 2 k ( k + 1 )
( 2 + 1 ) k = 1 ∑ n 2 k ( k + 1 ) = 2 n ( n + 1 ) ( n + 2 )
3 k = 1 ∑ n 2 k ( k + 1 ) = 2 n ( n + 1 ) ( n + 2 )
k = 1 ∑ n 2 k ( k + 1 ) = 3 × 2 n ( n + 1 ) ( n + 2 )
k = 1 ∑ n 2 k ( k + 1 ) = 6 n ( n + 1 ) ( n + 2 )
Thus we are seeking the 8th term which is 6 8 ( 9 ) ( 1 0 ) = 1 2 0 . In fact, we can generalise the nth term to be ( 3 n ) .